Association of circulating tumor cells and IMP3 expression with metastasis of osteosarcoma - Dai, Shuangwu; Shao, Xinxin; Wei, Qingzhu; Du, Shaohua; Hou, Changhe; Li, Haomiao; Jin, Dadi (Frontiers in Oncology, 2023)
Background Circulating tumor cells (CTCs) have been identified as a prognostic biomarker of tumors such as breast cancer and nasopharyngeal carcinoma, because they are obtained through a simple and noninvasive blood draw or liquid biopsy, but its clinical significance in osteosarcoma is still unclear. In this study, we analyzed the relationship between CTCs and clinicopathological features and discussed whether CTCs could be used as a biomarker for metastasis in osteosarcoma. Methods We enrolled 50 osteosarcoma patients with Enneking Stage IIB and Stage III and detected CTCs in 5 ml of peripheral blood samples collected from patients using the Canpatrol® CTC detection platform. Subsequently, multiplex RNA in situ hybridization (RNA-ISH) based on various molecular markers was performed to identify and classify CTCs. The relationships between clinical pathological features and CTC counts, subtypes (epithelial type, E type; hybrid epithelial/mesenchymal type, H type; mesenchymal type, M type), and insulin-like growth factor mRNA-binding protein 3 (IMP3) expression in CTCs were analyzed. Results CTCs were detected in 86% (43/50) of the osteosarcoma patients. The CTC counts, especially the total CTCs and H-type CTCs, signifcantly differed between Enneking Stage IIB and Stage III patients (P < 0.05). No significant differences were observed between the CTC count or type and other clinicopathological features (P > 0.05). There were significant differences in the expression of IMP3 in different types of CTCs, and the IMP3 positive rates in E/H/M type CTCs were 38.4, 65.6, and 62.0%, respectively (P < 0.001). Receiver operating characteristic (ROC) curve analysis showed that IMP3-positive CTC count had the best performance for diagnostic metastasis, with the largest area under the curve of 0.873 and cutoff value of four cells/5ml blood (sensitivity = 87.5%; specificity = 82.4%). Serial CTC monitoring in one patient suggested that total CTCs and H-type CTCs were associated with disease progression. Conclusion This study demonstrates that the CTCs, especially the IMP3-positive CTCs and H/M-type CTCs, are related to the metastasis of osteosarcoma.